"Work or fight!" : race, gender, and the draft in World War One - Shenk, Gerald E. (Palgrave Macmillan, 2005)
During World War I, the US demanded that all able-bodied adult men "work or fight." But fighting was mostly assigned to single white men who were not engaged in "productive" work. White men who were proper husbands and fathers, owned property, or worked at approved jobs, and who participated in civic activities, had the full benefits of citizenship without fighting. Women, men of color, and poor white men were often barred from achieving these benefits. This book uses the records of local draft boards and state draft officials in Georgia, New Jersey, Illinois, and California to tell the stories of men and women whose lives were touched by the Selective Service System.